(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article examines the integration and impact of virtual and augmented reality technologies in engineering graphics processes. Through a systematic literature review, case study analysis, and expert interviews, the study highlights significant benefits in visualization, collaboration, and education resulting from the adoption of VR and AR tools. Key findings demonstrate improvements in spatial comprehension, design communication, and project efficiency, while identifying challenges related to hardware costs, digital infrastructure, and skills development. The article concludes that VR and AR are central to the ongoing digital transformation of engineering graphics, with substantial implications for education, industry, and workforce development.